The Role of Competitive Advantage in Mediating the Effect of Market Orientation on Marketing Performance Florist in Denpasar City - Anak Agung Ayu Diah Puspita Mahadewi; I Gusti Agung Ketut Gede Suasana (International Journal of Social Science and Business, 2023)
The development of technology and information, causing customer demand in Denpasar for the Florist business has increased significantly. This demand is one of the factors that make business people competing to seize opportunities by establishing a Florist business. This study aims to explain the partial effect of market orientation on marketing performance and competitive advantage, explain the effect of competitive advantage on marketing performance, and explain the role of competitive advantage as a mediator of the influence of market orientation on  Florist  marketing performance in Denpasar City. This research was conducted at florists in Denpasar City with a total sample of 94 respondents using a questionnaire tool. The sample is determined using saturated sampling method. The data analysis technique used is path analysis with the help of the SPSS program. The results of the analysis show that market orientation has a positive and significant effect on marketing performance, market orientation has a positive and significant effect on competitive advantage, competitive advantage has a positive and significant effect on marketing performance. Another result is that competitive advantage is able to partially mediate the influence of market orientation on marketing performance. It is recommended that florist businesses in Denpasar City always strive to maintain good relations with customers and employees in the long run. This can be done by increasing market-oriented capabilities in running a business.